DDAH1 plays dual roles in PM2.5 induced cell death in A549 cells - Wang, Hongyun; Guo, Yuting; Liu, Limin; Guan, Longfei; Wang, Ting; Zhang, Luyao; Wang, Yue; Cao, Jianwei; Ding, Wenjun; Zhang, Fang; Lu, Zhongbing (Biochimica et biophysica acta, 2016)
Dimethylarginine dimethylaminohydrolase 1 (DDAH1) is an enzyme that can degrade asymmetric dimethylarginine (ADMA), an endogenous nitric oxide synthase (NOS) inhibitor. Emerging evidence suggests that alterations in the ADMA–DDAH1 pathway are involved in environmental pollution induced airway inflammation. However, the role of DDAH1 in protection against cytotoxicity of ambient airborne particulate matter is unclear. We examined the influence of DDAH1 expression on oxidative stress and cell apoptosis in human type II alveolar epithelial A549 cells exposed to PM2.5 (particulate matter with an aerodynamic diameter less than 2.5μM). We found that PM2.5 exposure for 48h significantly decreased DDAH1 expression. However, knockdown of DDAH1 prior to PM2.5 exposure actually attenuated the cytotoxicity of PM2.5. Cytoprotection in DDAH1 deficient cells was due to increased reactive oxygen species, activation of PI3K–AKT and mitogen-activated protein kinase (MAPK) pathways, subsequent activation of nuclear factor erythroid-2-related factor 2 (Nrf2) and this caused a subsequent reduction in PM2.5 induced oxidative stress relative to control. DDAH1 depletion also repressed the induction of inducible NOS (iNOS) in PM2.5-exposed cells and knockdown of iNOS protected cells against PM2.5 induced cell death. Interestingly, overexpression of DDAH1 also exerted a protective effect against the cytotoxicity of PM2.5 and this was associated with a reduction in oxidative stress and upregulation of the anti-apoptotic protein Bcl-2. Our data indicate that DDAH1 plays dual roles in protection against cytotoxicity of PM2.5 exposure, apparently by limiting PM2.5 induced oxidative stress. Our findings reveal new insights into the role(s) of the DDAH1/ADMA in pulmonary protection against airborne pollutants. This article is part of a Special Issue entitled Air Pollution, edited by Wenjun Ding, Andrew J. Ghio and Weidong Wu. [Display omitted] •PM2.5 decreased DDAH1 expression in A549 cells.•DDAH1 depletion ameliorates apoptosis and oxidative stress in PM2.5 exposed cells.•DDAH1 depletion induces Nrf2 nuclear translocation via multiple pathways.•Overexpression of DDAH1 attenuates PM2.5 induced oxidative stress and cell death.